APLIKASI PENDATAAN PASIEN DI PUSKESMAS SIPINTUANGIN - Lestari Pakpahan; Emma R. Simarmata; Mufria J. Purba (Universitas Methodist Indonesia, 2021)
Public health center is a health that requires computers as a means of processing and presenting information data. Puskesmas Sipintuangin services patient transactions daily. And there are several problems there, namely processing patient data still using manual methods, where the process takes a long time. In addition, there are also problems with archiving and ineffective reporting which results in repetition of the same data so that reports are often late, and the results are less accurate. To improve health services and actions towards patients, a Puskesmas data collection application is needed that can provide good and fast service to patients and is well managed and must remain coordinated.